Causes of mortality in military working dog from traumatic injuries - Storer, Amanda P.; Edwards, Thomas H.; Rutter, Christine R.; Young, Grace E.; Mullaney, Sara B. (Frontiers in Veterinary Science, 2024)
This study aimed to identify the pathophysiologic causes of death following traumatic injuries in military working dogs (MWDs) and determine the risk factors associated with mortality in MWD following traumatic injuries. Based on review of available data and supplemental records (when available), MWDs in which a definitive cause of death could be determined were included in the study population. These MWDs were assigned a cause of death based on categories previously identified in studies evaluating service member casualties. A group of MWDs who survived their traumatic injury and had similar mechanisms of injury and types of injury to the deceased MWDs were included to allow for comparison and establishment of risk factors associated with MWD death. Variables collected included breed, age, sex, mechanism of injury, survival/non-survival, type of trauma, mechanism of injury, pathophysiology that led to death and pre-hospital care provided. Statistical analysis included Fishers exact test for categorical variables and univariable and multivariable logistic regression to identify factors associated with the MWD death. A total of 84 MWDs (33 deceased and 51 living) were included in this study. Of the 33 MWDs that died, 27 (81.8%) were noted to be dead on arrival. The pathophysiologic causes of death were found to be hemorrhage (45.5% [n=15]), head trauma (21.2% [n=7]), catastrophic tissue destruction (15.2% [n=5]), pneumothorax (9.1% [n=3]) and one (3% [n=1]) of each of the following: septic shock, asphyxiation and burns. Military Working Dogs that did not receive non-DVM care were 3.55 times more likely to die than those that did receive non-DVM care (95% CI 1.03-12.27). In this population of MWDs, hemorrhage and head trauma were the most common pathophysiologic causes of death. The majority of MWDs died of their injuries before reaching veterinary care. To increase the survival of MWDs on the battlefield, further research should focus on developing new interventions and techniques to mitigate the effects of the pathophysiology noted to cause MWD death. Furthermore, given that care by a non-DVM was found to be associated with survival, the implementation of pre-hospital care should be a continued priority for those treating MWDs in the prehospital setting.